The Effect Of Communication, Leadership Style, And Organizational Culture On Employee Loyalty At PT Media Antar Nusa - Anisyah, Anggi Putri; Wakhyuni, Emi (Jurnal Fokus Manajemen, 2025)
Purpose : To determine whether communication, leadership style, and organizational culture influence employee loyalty at PT Media Antar Nusa. Research Methodology : This study employs a quantitative associative approach, utilizing questionnaires for data collection and multiple linear regression analysis for data analysis. Results : The findings reveal that communication, leadership style, and organizational culture each have a positive and significant impact on employee loyalty at PT Media Antar Nusa. Collectively, these factors also demonstrate a significant positive influence on employee loyalty. Contribution : This research offers practical implications for PT Media Antar Nusa to enhance employee loyalty through improved communication, participatory leadership, and aligning organizational culture with company values, reducing turnover. For researchers, it provides opportunities to apply management and organizational psychology theories while identifying gaps in prior studies. For future research, it opens avenues for exploration in other sectors or with additional variables, such as cultural alignment with workplace practices.